Accuracy of Injectable Kb Acceptor Re-Visit during the Covid-19 Pandemic in PMB Yayuk Handayani Wagir District Malang Regency - Rosyidah Alfitri; Astri Yunita (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2021)
The COVID-19 pandemic is a disease caused by coronavirus syndrome 2 (SARS-CoV-2) that attacks the respiratory system acutely, and caused more than 106 million people to become infected with more than 2.3 million deaths worldwide. In the family planning and birth control services (KB) service there is a revisit of kb active acceptor (old acceptors) and or visits of new acceptor is an effort to get contraceptive services aimed to prevent pregnancy. The purpose of our study was to see the difference in the accuracy of KB acceptor visits before and after the COVID-19 pandemic in Midwifery clinic (PMB) Yayuk Handayani Wagir District of Malang Regency. This research was quantitative research using experimental quasi research design with a pre post design approach. The sample in the study was the same as the study population of 50 injectable birth control acceptors in BPM Yayuk Handayani Wagir Magelang Regency. Research techniques use total sampling. In this data analysis, the normality test was carried out first, then the bivariate test used the dependent sample t-test. The results of the analysis test showed that before the COVID-19 pandemic, there were 43 revisits for active acceptors who matched the return date, while during the COVID-19 pandemic, 7 people were late for return visits and 11 people did not return for revisits. Obtained a value of p value of 0.000 which is less than 0.05 so it can be concluded there is a difference in the accuracy of visits before and during the COVID-19 pandemic. It can be concluded that there is a difference in the return visit of hormonal contraceptive acceptors in PMB Yayuk Handayani Wagir District of Malang Regency.